Kajian Optimasi Jaringan Long Term Evolution (LTE) Menggunakan Metode Physical Tuning di Kelurahan Bojong Nangka - Rummi Santi Rama Sirait (KILAT, 2020)
Kelurahan Bojong Nangka is a sub-urban area and an area that requires good network quality, where the quality of the telecommunications network is a supporting factor for the success of any communication activity. The network condition in Bojong Nangka Urban Village is still less than optimal, the results of the drive test on the existing network show that several areas in the Bojang Nangka Village have poor network quality. To improve the quality of the network in the research area, network optimization was carried out using the Physical Tuning method, namely adjusting tilting, re-azimuth, and increasing antenna height. The optimization results are simulated using Atoll software. The optimization results show an improvement in network quality by looking at network parameters, namely RSRP, SINR, and RSRQ. The percentage value of RSRP increased from 82.32% to 83.51%, for SINR it decreased from 89.51% to 86.8%, and RSRQ increased from 19.6% to 20.7%. From the calculation and simulation results as a whole shows an increase in network quality, seen from the percentage value of RSRP, SINR, and RSRQ.